INNV-34. INNOVATIVE, INDEPENDENT, PATIENT ADVOCATE ROLE ESSENTIAL THROUGHOUT DRUG DEVELOPMENT IN THE AGE OF SOCIAL MEDIA. (5th November 2018) - Lovely, Mary
Abstract: BACKGROUND: A mid-sized biotech company recruiting for high-grade glioma (HGG) clinical trials used the internet for patient awareness. Many patients and families began contacting the company inquiring about trials. METHOD: To offer ethical, informative responses, the company engaged a dedicated, independent patient advocate consultant to interact with the patients and families. This role provides critical separation from the drug company, maintaining patient privacy and preventing recruitment bias. The patient advocate role has evolved into a position that influences all the patient-oriented aspects of the research process. The patient advocate reviews all patient facing documents and provides patient perspectives. The patient advocate informs patients and families about the trial and provides support resources when appropriate. This role requires experience with the brain tumor population and evidence-based knowledge of patient and family needs. The patient advocate communicates with patients and caregivers and helps them navigate through the clinical trials research process. Also, the patient advocate liaises between the drug company and brain tumor advocacy groups. RESULTS: Activities performed since 2014 by Tocagens patient advocate included: A) communicated with > 1200 patients and caregivers through email and phone inquiries; B) reviewed clinical trial protocols, consents and brochures for patient and caregiver suitability; C) participated in the clinical trial patient recruitment team; D) wrote blogs related to living with a brain tumor and understanding clinical trials placed on the company site; E) communicated with brain tumor advocacy groups. CONCLUSION: A patient advocate consultant embedded in a biotech firm provides essential patient-centered perspective throughout drug development. This innovative, independent position provides an interface for patients and families to receive quality, individualized responses to questions. Clinical trial protocols become patient-oriented at times leading to more efficient patient recruitment and trial design. People inquiring about clinical trials receive accurate information, resources with a humane touch.